Regulatory and Institutional Approach in Tackling Marine Plastic Pollution: The Practice of Indonesia - Puspitawati, Dhiana; Susanto, Fransiska A.; Kurniaty, Rika; Kurniawan, Andi; Nursasmita, Muhammad Akbar; Mohd Rusli, Mohd Hazmi (Jurnal Suara Hukum, 2025)
Marine Plastic Pollution (MPP) is increasing at an alarming rate. It presses environmental crisis, posing significant threats to both marine ecosystem and biodiversity, as well as human health. While relevant international legal frameworks call for concerted global action, effective national law enforcement remains a crucial element in the fight against plastic waste. This research explores Indonesia’s practice in implementing existing international legal frameworks nationally to tackle MPP. Although Indonesia has made significant progress in establishing national laws that align with international legal frameworks, however, much remain to be done. This especially related to regulatory framework and law enforcement institutions. This paper highlights existing regulatory and institutional frameworks adopted by Indonesia and analyses key enforcement challenges faced by Indonesia in reducing MPP. It is argued that strengthening national enforcement mechanisms, fostering intergovernmental collaboration, and enhancing public-private partnerships are essential to curbing marine plastic pollution. Ultimately, the paper calls for a more robust, integrated approach that aligns national legal frameworks with global efforts to protect marine environments from further degradation.